Research Trends in Pragmatics and Discourse Analysis in the Field of Slavic Linguistics - Perelmutter, Renee; E. Borowski, Krzysztof (Slavia Centralis, 2022)
This article surveys recent trends and directions in pragmatics and discourse analysis-related research of Slavic languages. Within the subfield of pragmatics, the article surveys studies of facework/(im)politeness, hate speech, speech acts, and pragmatics of emotions. The discourse analysis section surveys such topics as discourse markers, bilingualism, deixis, evidentiality and stance, humor, turn-taking, and critical discourse analysis (CDA) / critical discourse studies (CDS). The article also outlines areas in need of more research for Slavists – these include facework and power in institutional contexts, pragmatics and L2 learning of Slavic languages, and bilingual/multilingual discourse and pragmatics.